Locus Ceruleus Norepinephrine Release: A Central Regulator of CNS Spatio-Temporal Activation? - Atzori, Marco; Cuevas-Olguin, Roberto; Esquivel-Rendon, Eric; Garcia-Oscos, Francisco; Salgado-Delgado, Roberto C.; Saderi, Nadia; Miranda-Morales, Marcela; Treviño, Mario; Pineda, Juan C.; Salgado, Humberto (Frontiers in Synaptic Neuroscience, 2016)
Norepinephrine (NE) is synthesized in the Locus Coeruleus (LC) of the brainstem, from where it is released by axonal varicosities throughout the brain via volume transmission. A wealth of data from clinics and from animal models indicates that this catecholamine coordinates the activity of the central nervous system and of the whole organism by modulating cell function in a vast number of brain areas in a coordinated manner. The ubiquity of NE receptors, the daunting number of cerebral areas regulated by the catecholamine, as well as the variety of cellular effects and of their timescales have contributed so far to defeat the attempts to integrate central adrenergic function into a unitary and coherent framework. Since three main families of NE receptors are represented – in decreasing order of affinity for the catecholamine – by: 2 adrenoceptors (2Rs, high affinity), 1 adrenoceptors (1Rs, intermediate affinity), and  adrenoceptors (Rs, low affinity), on a pharmacological basis, and on the ground of recent studies on cellular and systemic central noradrenergic effects, we propose that an increase in LC tonic activity promotes the emergence of four global states covering the whole spectrum of brain activation: 1) sleep: virtual absence of NE, 2) quiet wake: activation of 2Rs, 3) active wake/physiological stress: activation of 2- and 1Rs, 4) distress: activation of 2-, 1-, and Rs. We postulate that excess intensity and/or duration of states 3) and 4) may lead to maladaptive plasticity, causing – in turn – a variety of neuropsychiatric illnesses including depression, schizophrenic psychoses, anxiety disorders, and attention deficit. The interplay between tonic and phasic LC activity identified in the LC in relationship with behavioral response is of critical importance in defining the short- and long-term biological mechanisms associated with the basic states postulated for the central nervous system. While the model has the potential to explain a large number of experimental and clinical findings, a major challenge will be to adapt this hypothesis to integrate the role of other neurotransmitters released during stress in a centralized fashion, like serotonin, acetylcholine, and histamine, as well as those released in a non-centralized fashion, like